Vloga učiteljev športne vzgoje pri zagotavljanju prve pomoči v osnovi šoli - Slabe, Damjan (Šport (Ljubljana), 2019)
Despite preventive measures, primary schools are an environment where the risk of children accidents exists. The injuries are mainly related to sports activities. The purpose of the research is to determine the role of physical education teachers in the providing first aid (FA) in a primary school. Data collection was conducted using an anonymous questionnaire during the 2018/2019 school year. 257 sports teachers of Slovenian primary schools completed the survey. Physical education teachers consider that of all employees they should be the most qualified to give FA. In the past school year, almost all physical education teachers have faced a case of abrasion and almost one half with allergies as well. Respondents rate their knowledge of FA in case of ankle sprain (minor injury) as the highest level and in the case of spinal injury (severe injury) as the lowest level of knowledge. Most (93 %) of the surveyed teachers would attend FA courses in future what indicates their high motivation for renewing FA knowledge. Based on the findings, we conclude that physical education teachers play a very important role in providing FA in primary schools. In the event of a child accident in school, sports teachers are key FA givers, but not the only ones.
Keywords: first aid; injury; physical education teacher; poškodbe; prva pomoč; pupils; učenci; učitelji športne vzgoje